Pembuktian Berdasarkan Keterangan Ahli dan Visum Et Repertum pada Perkara Aborsi Menurut Undang-Undang Kesehatan - Wischa Intansari; Bambang Santoso, S.H., M.Hum (Sebelas Maret University, 2019)
This study aims to determine the suitability of the prosecution to prove the charges based on the testimony of experts and a post mortem cases of abortion with the provisions of article 184 of the Criminal Procedure Code in conjunction with Article 189 paragraph (2) f of Health Law and the suitability of the legal reasoning of judges deciding cases abortion declare the defendant guilty and convict with article 183 in conjunction with article 193 paragraph (1) criminal Procedure Code. The research method used is doctrinal legal research. Source materials used law is the primary legal materials and secondary law, with legal materials analysis techniques using syllogistic method and interpretation by using a pattern of deductive reasoning. In this study, it has been known that prosecution proving in a criminal act of abortion based on the testimony of experts and a post mortem on the condition of the accused and the dead fetus victims where the inspection results made by the competent authority on the basis of his knowledge and signed under oath, so that it becomes an authentic Act automatically become legitimate instrument of evidence and have value of proof strength however must be associated with the other evidence in order to created a truth materially in accordance with Article 133 and Article 184 paragraph (1) letter c of the Criminal Procedure Code and the judge in imposing a decision has been Obtain confdence based on at least two valid evidences, namely expert information, letters and statements of the accused.Keywords: Proof, Expert Description, Judge Consideration